2022
DOI: 10.3390/molecules27113458
|View full text |Cite
|
Sign up to set email alerts
|

Gel Property of Soy Protein Emulsion Gel: Impact of Combined Microwave Pretreatment and Covalent Binding of Polyphenols by Alkaline Method

Abstract: This study investigated the effects of microwave modification, alkali polyphenol (ferulic acid) covalently combined modification, and microwave-alkali polyphenol covalently combined modification on the gel properties of soy protein emulsions. The results showed that the properties of soy protein emulsions were improved significantly by the three modification methods. After three kinds of modification, the viscoelasticity of soy protein emulsion gel increased, and a gel system with stronger elasticity was forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The smaller the relaxation time, the tighter the binding of water and substance 41 . T 21 (< 10 ms) represents bound water tightly bound to the macromolecule; T 22 (10–100 ms) represents partially immobile water, distributed in the network structure of the protein; and T 23 (100–10 000 ms) represents free water, located outside the protein network structure 42,43 . Figure 3 and Table 3 show T 2 of the mixed gels with different ratios, and three hydrogen proton peaks ( T 21 , T 22 and T 23 ) could be clearly observed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The smaller the relaxation time, the tighter the binding of water and substance 41 . T 21 (< 10 ms) represents bound water tightly bound to the macromolecule; T 22 (10–100 ms) represents partially immobile water, distributed in the network structure of the protein; and T 23 (100–10 000 ms) represents free water, located outside the protein network structure 42,43 . Figure 3 and Table 3 show T 2 of the mixed gels with different ratios, and three hydrogen proton peaks ( T 21 , T 22 and T 23 ) could be clearly observed.…”
Section: Resultsmentioning
confidence: 96%
“…41 T 21 (< 10 ms) represents bound water tightly bound to the macromolecule; T 22 (10-100ms) represents partially immobile water, distributed in the network structure of the protein; and T 23 (100-10 000 ms) represents free water, located outside the protein network structure. 42,43 Figure 3 and Table 3 show T 2 of the mixed gels with different ratios, and three hydrogen proton peaks (T 21 , T 22 and T 23 ) could be clearly observed. From Table 3, it was found that A 21 ranged from 6.35 to 38.42, and the addition of chicken breast caused a significant decrease in A 21 (P < 0.05).…”
Section: Low-field Nmrmentioning
confidence: 97%
“…The presence of the aqueous phase may change the interfacial membrane structure of the protein‐coated droplets through the electrostatic shielding effect, thus affecting the stability of the emulsion. The decrease of electrostatic repulsion between adsorbed particles and non‐adsorbed particles may strengthen the interfacial film (Xu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The parameter settings of the refractive indices were oil phase (1.46) and water phase (1.33). Samples were diluted 100-fold with deionized water to avoid multiple scattering effects and used for analysis [ 47 ].…”
Section: Methodsmentioning
confidence: 99%